AKTIVITAS ANTIBAKTERI FRAKSI ETIL ASETAT DAUN JAMBU AIR (Syzygium aqueum) TERHADAP Shigella dysentriae - Pupunk Fajriyani; Aulia Nur Rahmawati; Novena Yety Lindawati (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2022)
Shigella dysentriae is a genus of Shigella which has a high percentage of causing dysentery by 25%. The ethyl acetate fraction of guava leaves has potential as an antibacterial because the amount of compounds that provide antibacterial activity are more attracted in this solvent. The purpose of this study was to see the potential for inhibition of the ethyl acetate fraction of guava leaves (Syzygium aqueum) at each variation of its concentration against the bacterium Shigella dysentriae. The ethyl acetate fraction was obtained by liquid-liquid fractionation. The ethyl acetate fraction was tested in the zone of inhibition against Shigella dysentriae with various concentrations of 12.5%, 25%, 50%, and 100%, Ciprofloxacin positive control and 100% DMSO negative control. The data obtained were processed using One Way Anova with a 95% confidence level. The results of phytochemical screening of the ethyl acetate fraction of guava leaves showed positive for flavonoids, alkaloids, tannins, saponins, and steroids. Inhibition test of ethyl acetate fraction of guava leaves against bacteria Shigella dysentriae had the smallest inhibitory power at a concentration of 12.5%, the inhibitory power was 6.3 mm; 25% concentration of 15.3 mm; 50% concentration of 16.7 mm; and the concentration of 100% the largest inhibitory power was 18.4%. The results of the antibacterial inhibition of the ethyl acetate fraction of guava leaves had a significant difference in each concentration with a significance value (p <0.05).